Coupled ocean-atmosphere dynamics of the 2017 extreme coastal El Niño - Qihua Peng (Nature Portfolio, 2019)
The extreme coastal El Niño of March 2017 caused devastating flooding in coastal Peru but its mechanism remains unclear. Here the authors investigate the physical processes using observations and model simulations and suggest that such extreme coastal flooding is predictable and will become more frequent as climate warms.